Upaya Guru Dalam Meningkatkan Anak Slow Learner Dalam Pembelajaran Di SDN Baddurih - Febri Dwiyanto; Nova Estu Harsiwi (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Learning for children with special needs has its own method according to their needs. Not only children with special needs have needs, but also all children have needs. One of them is education. The aim of this research is to find out how teachers work in handling children who have special needs, especially those who are Slow Learners in learning. The method used in this research is to use a qualitative method with a descriptive approach. In collecting data, researchers used interviews and observations conducted at Baddurih Elementary School. In the results of interviews that have been conducted, the teacher's efforts to handle children who are slow learners are by using special strategies, namely by using an individual approach and a remedial approach in the learning process.